Growing concerns of emissions from the burning of biomass residues have led to a demand for more efficient technologies to mitigate the effect of excess residues. The moisture content of the biomass used decreased from 8.1% to 5.5% after the torrefaction - E. Eseyin, Anthonia; Uzoeshi, Tochukwu; R. Gungshik, John; R. Gungshik, John; E. Ankwai, Godwin; E. Ankwai, Godwin; Ibrahim, Mohammed; Ibrahim, Mohammed (International Journal of Advanced Chemistry, 2021)
Growing concerns of emissions from the burning of biomass residues have led to a demand for more efficient technologies to mitigate the effect of excess residues. The moisture content of the biomass used decreased from 8.1% to 5.5% after the torrefaction process. Results of the % volatile content indicated a significant reduction from 70.05% to 12.4%. The ash content increased from 5.25% to 10.7%, the percentage amount of fixed carbon increased significantly, from 16.6% to 71.4%. % C increased from 46.51% to 65.15%, while % O reduced significantly from 47.44% to 29.57%. There was a slight increase in % N, with a reduction in % H. Torrefied corn stalks were applied to soil samples, using three different application rates (1%, 3% and 5% w/w). The addition of torrefied corn stalks led to increase in soil pH across all 3 treated samples. Electrical conductivity values increased from the control value of 1.87 to as high as 4.05. There were also positive improvements in the cation exchange capacity and water holding capacity of all treated soil samples. Treatment of soil with torrefied biomass improved soil quality significantly, with the potential of fostering food security.Â Â